DAKWAH ISLAM DI ERA GLOBALISASI PERSPEKTIF BIMBINGAN PENYULUHAN ISLAM - Hemlan Elhany (Jurnal Bimbingan Penyuluhan Islam, 2019)
preaching can also be or can be done by having a good behavior or by the existence of a social action. Historically it can be seen that Islamiyah is the center of the activities carried out by the preacher, then it seems impossible there will be the biggest outbreak of Muslims in Indonesia as we know it. Islamic da'wah has two challenges, namely the propaganda scholarship which is yet to provide an encouraging look for the community. Second, the probelem or challenge of the oral preaching practice dominates the arena of a stage in the use of the results of scientific and technological thinking. The use and acceptance of the results of the creation of human reason in the form of science and technology is a form of gratitude to the creator. The results of technological advances can also be used as a means of creating human well-being. In connection with da'wah, advances in information technology, television, for example, are very appropriate in making the media in the diffusion process of Da'wah to long-distance Da'wah already very developed in Indonesia, there are already many young preachers, who preach well in the media mass or to the area. Because in terms of inviting goodness and in preaching messages